The Opportunities of Green Intellectual Capital for Industrial Sustainability: A Systematic Review - Indriana Damaianti (Sainteks: Jurnal Sain dan Teknik, 2022)
This paper aims to describe the evolution of research on green intellectual capital in exploring opportunities for future research directions. An author will try to clarify knowledge about the application of the green intellectual capital paradigm by reviewing the findings about the results achieved by industries that apply the green intellectual capital paradigm and the factors that enhance this process. A systematic review was carried out involving a final sample of a total of 23 articles published from 2011 to 2021. The database sources used in this study were Emerald, Science Direct, Publish or Perish with API Key based on a set of inclusions/exclusions for analysis and synthesis in meeting the paper's objectives. The findings suggest that green intellectual capital offers a significant framework for promoting sustainability in the industry. Despite highlighting the increasing trend of green intellectual capital, it turns out that there is still little reliable data on this issue, especially discussing the role of green intellectual capital as a framework for promoting sustainability in the industry. This paper seeks to contribute to and analyze limited articles on green intellectual capital and identify areas for further research. In theory, it would be possible to synthesize the results of green intellectual capital as an illustration of how it affects the industry and the environment. Practitioners are expected to open an understanding of the actual results of green intellectual capital to overcome the gap between theory and practice, make this value more accessible to practitioners and managers, and choose green concepts in their industry.